The effectiveness socialization of the Kurikulum Merdeka independently change in high schools Siak District - Wenny Fitria; Dadang Sukirman (Inovasi Kurikulum, 2023)
In the 2022/2023 school year, the Ministry of Education, Culture, and Research provides an opportunity for schools not Sekolah Penggerak to implement the Kurikulum Merdeka independently. Government support for schools that implement the IKM independently change is provided primarily by the Platform Merdeka Mengajar (PMM). In PMM, all information about the Kurikulum Merdeka is available and can accessed by teachers and schools. Socialization of the Kurikulum Merdeka is no longer provided through training and education, but teachers and schools learn independently by accessing the platform. Although PMM is a breakthrough in the world of Indonesian education, the implementation at the education unit level still reaps the pros and cons. There are still many teachers in Indonesia who are unaware of this government program regarding PMM. Using a qualitative method, the author wants to know how the effectiveness of the socialization of the Kurikulum Merdeka through PMM in schools in Siak District that implement the Kurikulum Merdeka through independent change. The results showed that using PMM in these schools was not optimal, teachers preferred that the socialization be carried out face-to-face with a capabilities trainer. AbstrakPada tahun ajaran 2022/2023 Kemendikbudristek memberi kesempatan kepada sekolah yang bukan Sekolah Penggerak untuk menerapkan Kurikulum Merdeka secara mandiri. Dukungan utama yang diberikan pemerintah kepada sekolah yang menerapkan IKM jalur mandiri adalah dengan menyediakan Platform Merdeka Mengajar (PMM). Di PMM tersedia semua informasi tentang Kurikulum Merdeka yang bisa diakses oleh guru dan sekolah. Sosialisasi mengenai Kurikulum Merdeka tidak lagi diberikan melalui diklat-diklat dan pelatihan berjenjang, melainkan guru dan sekolah belajar mandiri dengan mengakses platform tersebut. Walaupun PMM merupakan terobosan baru di dunia pendidikan Indonesia, tetapi penerapan dan penggunaannya di lapangan, masih menuai pro dan kontra. Masih banyak guru-guru di Indonesia yang belum mengetahui program pemerintah mengenai PMM ini. Dengan menggunakan metode kualitatif, penulis ingin mengetahui bagaimana efektivitas sosialisasi Kurikulum Merdeka melalui PMM di sekolah-sekolah di Kabupaten Siak yang menerapkan Kurikulum Merdeka melalui jalur mandiri berubah. Hasil penelitian menunjukkan bahwa penggunaan PMM di sekolah-sekolah tersebut belum maksimal, masih banyak guru yang tidak mengetahui keberadaan PMM tersebut, guru-guru lebih memilih sosialisasi dilakukan secara tatap muka dengan narasumber yang mempunyai kapabilitas di bidangnya.Kata Kunci: Kurikulum Merdeka; Platform Merdeka Mengajar; sosialisasi Kurikulum Merdeka